Memória e identidade cultural na poética do compostor sertanejo Goiá - Braz, Gláucia Helena (2020)
This research aims to expand the literary studies about the poetic-musical work of Gerson Coutinho da Silva (1935-1981), known artistically as Goiá. For this purpose, we take as reference the memory and cultural identity present in the artist's songs and poems - productions timidly contemplated in contemporary academic studies, which justifies the relevance of the present study. Anchored in the light of Literary Theory in conjunction with Music Studies and considering the specificity of the genre “song”, we also resort to interdisciplinary knowledge from other areas, such as: History, Geography, Philosophy, Sociology, Prosody and Phonetics, in the search to explain a greater range of potentialities of our research object. The challenge of this study was to prove that the poetics of Goiá is located at the intersection of Literature and memory, revealing cultural and peculiar evidence of the interior community. Absent from the lands of Minas Gerais in search of the dream of becoming prominent in his musical career, in the 1960s and 1970s, the composer Goiá produced several songs that rescue the singularities of the Minas Gerais hinterland, in particular, of his native land, Coromandel-MG: its natural beauty, its customs and beliefs, as well as the language of the people that reflects the hospitality, humor and charisma of the sertanejo. Seeking to prove these characteristics, we undertook the analysis of nine songs by the artist and five of his tribute poems, recorded in the book O poeta Goiá, by Lúcio Flores (2004), through the bias of the manifestations of the individual memory of the author, added to the more of society: collective memory. Along this path, we seek to outline the artist's trajectory towards success, as well as the history of country and country music in our country, contextualizing the composer and his poetics. Along this route, we visited the artist's homeland, getting to know some of the scenarios described in his songs and talked with some residents of the city of Minas Gerais, who met the composer. Next, we tried to outline the artist's trajectory towards success, as well as the history of country and country music in our country, contextualizing the author and his poetics. In this sense, as theoretical assumptions, we resort, especially, to the following conceptions and authors: concepts of memory and autobiography, coined by Bosi (1994), Halbwachs (2003), Lejeune (2004) and Brandão (2006); we are also looking for studies on the biography of Goiá, developed by Flores (2004), Reis (2009), Brito (2010) and Martins; Hordones (1996); about the history of country music / roots, we use the concepts postulated by and Romildo Sant'Anna (2009), Paula (2013), Peripato (2008), Sautchuk (2015), Antunes (2013), Reis (2009) and Gutemberg ( 2011); we also resort to the theoretical assumptions about poem, song and literature, made by Tavares (2005), Bosco (2006), Finegan (2008), Solange Ribeiro (2002) and Luiz Tatit (1996); about voice, oral poetry, culture, performance and reception, we seek bibliographic support developed by Paul Zumthor (1999). At the end of the research, the importance of Goiá's poetics for Brazilian culture became evident, as well as the harmonious combination of poetry and music in the artist's work, revealing our “plurality of identities”.